Individual and organizational predictors of health care aide job satisfaction in long term care. Issue 1 (December 2016) - Chamberlain, Stephanie; Hoben, Matthias; Squires, Janet; Estabrooks, Carole
Abstract Background Unregulated health care aides provide the majority of direct health care to residents in long term care homes. Lower job satisfaction as reported by care aides is associated with increased turnover of staff. Turnover leads to inferior job performance and negatively impacts quality of care for residents. This study aimed to determine the individual and organizational variables associated with job satisfaction in care aides. Methods We surveyed a sample of 1224 care aides from 30 long term care homes in three Western Canadian provinces. The care aides reported their job satisfaction and their perception of the work environment. We used a hierarchical, mixed-effects ordered logistic regression to model the relative odds of care aide job satisfaction for individual, care unit, and facility factors. Results Care aide exhaustion, professional efficacy, and cynicism were associated with job satisfaction. Factors in the organizational context that are associated with increased care aide job satisfaction include: leadership, culture, social capital, organizational slack—staff, organizational slack—space, and organizational slack—time. Conclusions Our findings suggest that organizational factors account for a greater increase in care aide job satisfaction than do individual factors. These features of the work environment are modifiable and predict care aide job satisfaction. Efforts to improve care aide work environment and quality of care should focus on organizational context.